Scientific-Consensus Communication About Contested Science: A Preregistered Meta-Analysis. (December 2022) - van Stekelenburg, Aart; Schaap, Gabi; Veling, Harm; van 't Riet, Jonathan; Buijzen, Moniek
Scientific-consensus communication is among the most promising interventions to minimize the gap between experts' and the public's belief in scientific facts. There is, however, discussion about its effectiveness in changing consensus perceptions and beliefs about contested science topics. This preregistered meta-analysis assessed the effects of communicating the existence of scientific consensus on perceived scientific consensus and belief in scientific facts. Combining 43 experiments about climate change, genetically modified food, and vaccination, we found that a single exposure to consensus messaging had a positive effect on perceived scientific consensus ( g = 0.55) and on belief in scientific facts ( g = 0.12). Consensus communication yielded very similar effects for climate change and genetically modified food, whereas the low number of experiments about vaccination prevented conclusions regarding this topic. Although these effects are small, communicating scientific consensus appears to be an effective way to change factual beliefs about contested science topics.